Zasadność współczesnych klasyfikacji genologicznych kolekcji „Listów Ksenofonta” oraz „Listów Sokratesa i sokratyków”. Pomiędzy nowelą a powieścią - Marchewka, Anna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
This article is an attempt to indicate the genre of two collections of the apocryphal letters – The letters of Xenophon (we only have 7 excerpts preserved in the Anthology by Stobaeus) and The letters of Socrates and the Socratics. The term griechische Briefroman proposed by N. Holzberg to describe the genre of pseudonymous collections of letters in most cases proved to be too wide and inadequate. P.A. Rosenmeyer found the term novella more appropriate here. So, what literary characteristics, inherent in a novel or a novella or a short story, are dominant in Xenophontis epistolae and Socrates et socraticorum epistolae?